Stage bus operational practices: KL-Klang bus company / Zainura Jaafar - Jaafar, Zainura (2022)
KL Klang & Port Swettenham Omnibus Co. Bhd a as major stage bus provider in Klang Valley plays a major role in providing services to public. It is considered one of leading subsidiary company of Park May Berhad providing city bus services. The company have to take challenges in providing an efficient and reliable service to strive in the very competitive environments. Identification of the present operational practice will deter how the company would look towards improving its operational efficiency to meet the operational standards.